2008
DOI: 10.1029/2006wr005859
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous behavior of soil mantle groundwater demonstrates the major effects of bedrock groundwater on surface hydrological processes

Abstract: The formation of groundwater in the soil mantle has a dominant effect on rainwater discharge and shallow landslide occurrence in headwater catchments. Here, we report two completely different groundwater responses within a single well excavated into the soil mantle. One was an ephemeral‐type response that is well described by physical hydrology models based on a geographic information system (GIS). The other was a semi‐perennial‐type response, rarely reported in previous studies, which cannot be explained by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…Below 54 cm, the soil mantle contained many gravels reaching approximately 30 cm in diameter. Three 100-mL soil core samples collected between the gravels had K s values ranging from 1.1 Â 10 À1 to 1.9 Â 10 À1 cm s À1 [Kosugi et al, 2008]. For more information on the experimental watershed, see Kosugi et al [2008].…”
Section: Study Sitementioning
confidence: 99%
See 4 more Smart Citations
“…Below 54 cm, the soil mantle contained many gravels reaching approximately 30 cm in diameter. Three 100-mL soil core samples collected between the gravels had K s values ranging from 1.1 Â 10 À1 to 1.9 Â 10 À1 cm s À1 [Kosugi et al, 2008]. For more information on the experimental watershed, see Kosugi et al [2008].…”
Section: Study Sitementioning
confidence: 99%
“…Kosugi et al [2008] reported that soil mantle groundwater in a single well in this watershed showed two completely different responses. One response involved ephemeral-type groundwater (referred to as ''EG'' in this study), which was generated only during rainfall events and disappeared rapidly after the events ceased.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations